Development and characterization of crackers with ginger (Zingiber officionale) and turmeric (Curcuma longa) extracts. - Lacson, Kristina Samantha Bermejo (2018.)
The study focused on developing Ginger - Turmeric (GT) crackers. Three different formulations were prepared with varying ratios of ginger to turmeric extracts. Among the three ratios: ratio 1:1, ratio 3:2, and ratio 2:3, ratio 2:3 yielded the most preferred GT cracker; it was significantly the most preferred (Kramer?s rank sum test at 5% level of significance). This was subjected to proximate analysis, water activity determination, texture profile analysis for hardness, caloriifc value determination, and sensory evaluation. The GT cracker had 1.90% moisture, 3.82% ash, 1.74% fat, 0.28% crude fiber, 10.54% protein content, 81.65% carbohydrates, and 385.70 Cal calorific value. Water activity was 0.123 and a hardness value of 2.90N. The product obtained a rating of like very much from a total of 100 respondents, and significantly had a higher acceptability rating in the age group of 25 years old above. Forty percent of the total respondents rated it like very much, 28% rated it as like moderately, and 13% as like extremely.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Ginger; Zingiber officionale; Turmeric; Curcuma longa; Ginger-turmeric extract -- Cracker production